Réponses

2013-01-10T21:56:17+01:00

Bonsoir

pour le 7

a) 

5x-2 = 4-2x-7x

5x+9x = 6

14x = 6

x = 6/14 = 3/7

b)

4(x-3)-5(x+6) = 0   il suffit que l'un des facteurs soit égal à 0

soit

x-3 = 0  donc x= 3

ou 

x+6 = 0 donc x= -6 

c)

(3x-1)(2+3x) = (3x-5)²

9x²+3x-2 = 9x²+25-30x

33x = 27

x = 27/33 on peut simplifier par 3

x = 9/11

d)

x/6+1/4 =(7/12 *x) -1 

2x/12 -7x/12 = -1-1/4

-5/12x = -5/4

x = (-5/4)(-12/5)

x = 60/20

x = 3 

e) illisible (flash)

f)

4-(x+6)/5 = 3x/10-1/5

(2x+12)/10 = 3x/10-1/5 

(2x+12-3x)/10 = - 1/5 - 4 

x/10 = -21/20

x= (10*21)/20 - 240/20 

x= 30/20

x= 3/2